INOVASI PIMPINAN PESANTREN DALAM PENGELOLAAN SARANA DAN PRASARANA DI PONDOK PESANTREN BAITUL IHSANI NAHDATUL WATHAN KECAMATAN TEBO TENGAH PROVINSI JAMBI - Tendri Indri Ani; Musli; Ahmad Fikri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the leadership innovations of the Baitul Ihsani Nahdlatul Wathan Islamic Boarding School in Tebo Tengah District, Jambi Province, in managing educational facilities and infrastructure. This study used a qualitative approach, with data collection techniques through observation, interviews, and documentation. The results indicate that the leadership implemented several forms of innovation, including the development of a more structured facilities management system, improved regular facility maintenance, and the use of simple technology to support learning activities. Supporting factors for innovation include leadership commitment, support from some teaching staff, and participation from the community and students' guardians. Inhibiting factors include limited funding, resistance from some teachers or students to change, and a lack of expertise in facilities management.